The Ethology of Domestic Animals: An Introductory Text, Modular Texts 2009
DOI: 10.1079/9781845935368.0161
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour of sheep and goats.

Abstract: This chapter presents the origin, history of domestication and breed development, economic importance, behaviour, management and welfare of sheep and goats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…The frequencies of mounting and butting increased in both groups, after the first month of the experimental period. Although it has been reported that 1‐month‐old kids may possess sexual behaviours that mature animals display (Ugur et al., 2004), we did not consider mounting in a sexual sense, as it was never accompanied by other sexual behaviours, such as those described by Dwyer (2009). An increase of aggressiveness may be associated with frustration and discomfort (Gonyou, 1994), but, in the present study, butting cannot be considered as aggressive behaviour, because not aimed at causing injury to another kid (Barroso et al., 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The frequencies of mounting and butting increased in both groups, after the first month of the experimental period. Although it has been reported that 1‐month‐old kids may possess sexual behaviours that mature animals display (Ugur et al., 2004), we did not consider mounting in a sexual sense, as it was never accompanied by other sexual behaviours, such as those described by Dwyer (2009). An increase of aggressiveness may be associated with frustration and discomfort (Gonyou, 1994), but, in the present study, butting cannot be considered as aggressive behaviour, because not aimed at causing injury to another kid (Barroso et al., 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Rumination generally occurs when the animals are lying or standing. During rumination the animals are in a state of drowsiness, and there has been speculation about whether ruminants do actually sleep (Dwyer 2009). In this study the activity of rumination was the least frequent activity in both grazer species.…”
Section: Discussionmentioning
confidence: 80%
“…La ausencia de restos de bóvido en el sitio de PP3-C se puede explicar por el elevado coste de mantenimiento y una tasa baja de reproducción de esta especie animal (Dwyer, 2016). Aunque pueden proporcionar una mayor fuente de ingresos que los ovicápridos, debido a la alta cantidad de biomasa que pueden suministrar, dependen de una alimentación más húmeda y selectiva (e.g.…”
Section: Discussionunclassified